2016
DOI: 10.1039/c5sm03008k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of cracking in drying colloidal sheets

Abstract: Colloidal dispersions are known to display a fascinating network of cracks on drying. We probe the fracture mechanics of free-standing films of aqueous polymer-particle dispersions. Thin films of the dispersion are cast between a pair of plain steel wires and allowed to dry under ambient conditions. The strain induced on the particle network during drying is relieved by cracking. The stress which causes the films to crack has been calculated by measuring the deflection of the wires. The critical cracking stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…have suggested that decreasing the yield stress of a suspension, could increase its fracture toughness by increasing the plastic dissipation around the crack tip. Sengupta and Tirumkudulu also have suggested that viscous dissipation in front of the crack tip influences crack dynamics, while Mattern et al . proposed the increased strength exhibited in wet bodies was due to the rearrangement of capillary bridges.…”
Section: Drying and Crackingmentioning
confidence: 99%
See 1 more Smart Citation
“…have suggested that decreasing the yield stress of a suspension, could increase its fracture toughness by increasing the plastic dissipation around the crack tip. Sengupta and Tirumkudulu also have suggested that viscous dissipation in front of the crack tip influences crack dynamics, while Mattern et al . proposed the increased strength exhibited in wet bodies was due to the rearrangement of capillary bridges.…”
Section: Drying and Crackingmentioning
confidence: 99%
“…[334][335][336] Recently, Goehring et al 336 have suggested that decreasing the yield stress of a suspension, could increase its fracture toughness by increasing the plastic dissipation around the crack tip. Sengupta and Tirumkudulu 337 also have suggested that viscous dissipation in front of the crack tip influences crack dynamics, while Mattern et al 338 proposed the increased strength exhibited in wet bodies was due to the rearrangement of capillary bridges. It has been observed that when the crack forms, the tip extends from the surface into the saturated area, 339 but it is not known how the cracks initiate.…”
Section: Drying and Crackingmentioning
confidence: 99%
“…3) it is also clear that shear bands only influence the motion of cracks in a material and are not a complete explanation of this phenomenon. A complete description of crack hopping is likely to depend on such factors as poroelasticity19 and a balance of the inertia and viscous dissipation that occur during crack propagation20. These would lead to increasing/decreasing stresses with time near the crack tip before/after hops71920.…”
Section: Resultsmentioning
confidence: 99%
“…A complete description of crack hopping is likely to depend on such factors as poroelasticity19 and a balance of the inertia and viscous dissipation that occur during crack propagation20. These would lead to increasing/decreasing stresses with time near the crack tip before/after hops71920. However, shear bands seem to provide an explanation for the stochastic nature of the dynamics in small particles of both silica and polystyrene and in determining the final position of crack tips.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments related to the relationship between crack areas and thicknesses are described in Ma and Burton [11]. In Reference [12], the crack evolution was studied in colloidal systems. References [13,14] considered the role of variable film thickness, and Romero et al [15] studied the fracture control of films.…”
Section: Introductionmentioning
confidence: 99%